Synthesis of porous, hollow metal MCO3 (M=Mn, Co, Ca) microstructures and adsorption properties thereof - Cai, Ren (2014)
Porous, hollow metal carbonate microstructures show many unique properties, and are attractive for various applications. Herein, we report the first demonstration of a general strategy to synthesize hollow metal carbonate structures, including porous MnCO3 hollow cubics, porous CoCO3 hollow rhombuses and porous CaCO3 hollow capsules. For example, the porous, hollow MnCO3 microcubes show larger Brunauer–Emmett–Teller (BET) surface areas of 359.5 m2 g−1, which is much larger than that of solid MnCO3 microcubics (i.e., 12.03 m2 g−1). As a proof of concept, these porous MnCO3 hollow microcubes were applied to water treatment and exhibited an excellent ability to remove organic pollutants in waste water owing to their hollow structure and large specific surface area.